Time factor role estimation in combined treatment of primary malignant brain tumours - Lazar, D. A.; Rozumenko, V. D. (Ukrainian Neurosurgical Journal, 2007)
The effectiveness of postoperative radiotherapy in patients with primary malignant brain tumours treatment was analysed. The dependence of life duration and quality, radio reactions frequency and severity on the terms of postoperative irradiation.